Infrared neural stimulation induces intracellular Ca2+ release mediated by phospholipase C. Issue 2 (9th August 2017) - Moreau, David; Lefort, Claire; Pas, Jolien; Bardet, Sylvia M.; Leveque, Philippe; O'Connor, Rodney P.
Abstract : The influence of infrared laser pulses on intracellular Ca 2+ signaling was investigated in neural cell lines with fluorescent live cell imaging. The probe Fluo‐4 was used to measure Ca 2+ in HT22 mouse hippocampal neurons and nonelectrically excitable U87 human glioblastoma cells exposed to 50 to 500 ms infrared pulses at 1470 nm. Fluorescence recordings of Fluo‐4 demonstrated that infrared stimulation induced an instantaneous intracellular Ca 2+ transient with similar dose‐response characteristics in hippocampal neurons and glioblastoma cells (half‐maximal effective energy density EC50 of around 58 J.cm −2 ). For both type of cells, the source of the infrared‐induced Ca 2+ transients was found to originate from intracellular stores and to be mediated by phospholipase C and IP3 ‐induced Ca 2+ release from the endoplasmic reticulum. The activation of phosphoinositide signaling by IR light is a new mechanism of interaction relevant to infrared neural stimulation that will also be widely applicable to nonexcitable cell types. The prospect of infrared optostimulation of the PLC/IP3 cell signaling cascade has many potential applications including the development of optoceutical therapeutics. Abstract : The ability of infrared laser exposure to stimulate intracellular Ca 2+ signaling is investigated in cell lines of neural origin. Fluorescence live‐cell Ca 2+ imaging with Fluo‐4 is used in HT22 mouse hippocampal neurons and U87 human glioblastoma cells. Activation of phospholipase C and IP3 ‐induced Ca 2+ release from the endoplasmic reticulum is identified as a common mechanism of infrared‐stimulated signaling in both the excitable and nonexcitable cell types tested.